Pengembangan Website "Budisah" dalam Meningkatkan Pemahaman Kebudayaan Islam Madinah pada Siswa Kelas IV SD - Nuuran Raudha Senja; Siti Choirun Nisa; Siti Fatimah Zahra; Ani Nur Aeni (ANWARUL, 2025)
This research aims to develop and evaluate the "BUDISAH" (Culture and History of the Migration of Prophet Muhammad SAW) website based on Google Sites as a learning media for Islamic Religious Education (PAI) for fourth-grade elementary school students. The research method used is Design and Development (D&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development process involves analyzing students' needs, designing a user-friendly interface, and integrating multimedia elements such as text, images, animated videos, and interactive quizzes. Implementation was conducted at Gunungsari Elementary School involving 16 fourth-grade students. Evaluation results indicate that this website received positive feedback from content expert validators, media experts, and students. The "BUDISAH" website is considered effective in enhancing students' understanding of the material on the migration of Prophet Muhammad SAW to Medina and in increasing students' interest in learning. However, there are some technical constraints, such as limited supporting devices, that affect the implementation. Overall, this website is deemed suitable for use as an innovative learning media at the elementary school level.